Cleaved β-Actin May Contribute to DNA Fragmentation Following Very Brief Focal Cerebral Ischemia. Issue 3 (2nd February 2018) - Ye, Zhouheng; Ander, Bradley P; Sharp, Frank R; Zhan, Xinhua
Abstract: Our previous study demonstrated caspase independent DNA fragmentation after very brief cerebral ischemia, the mechanism of which was unclear. In this study, we explore whether actin is cleaved following focal cerebral ischemia, and whether these structural changes of actin might modulate DNA fragmentation observed following focal ischemia. Results showed that a cleaved β-actin fragment was identified in brains of rats 24 hours following 10-minute and 2-hour focal ischemia. Though granzyme B and caspase-3 cleaved β-actin in vitro, the fragment size of β-actin cleaved by granzyme B was the same as those found after 10-minute and 2-hour focal ischemia. This was consistent with increases of granzyme B activity after 10-minute and 2-hour ischemia compared with controls. Cerebral extracts from 10-minute and 2-hour ischemic brains degraded DNA in vitro. Adding intact β-actin to these samples completely abolished DNA degradation from the 10-minute ischemia group but not from the 2-hour ischemia group. We concluded that β-actin is likely cleaved by granzyme B by 24 hours following 10-minute and 2-hour focal cerebral ischemia. Intact β-actin inhibits DNase, and cleavage of β-actin activates DNase, which leads to DNA fragmentation observed in the brain following very brief focal ischemia.